Are deep‐ocean‐generated surface‐wave microseisms observed on land?. Issue 7 (25th July 2013) - Bromirski, Peter D.; Stephen, Ralph A.; Gerstoft, Peter
Abstract [1] Recent studies attribute land double‐frequency (DF) microseism observations to deep water generation. Here we show that near‐coastal generation is generally the dominant source region. This determination is based on observations at land and ocean seismic stations, buoys, gravity‐wave hindcasts, and on beamforming results from continental seismic arrays. Interactions between opposing ocean wave components generate a pressure excitation pulse at twice the ocean wave frequency that excites pseudo‐Rayleigh (pRg) wave DF microseisms. pRg generated in shallow coastal waters have most of their energy in the solid Earth ("elastic" pRg) and are observed by land‐based and seafloor seismometers as DF microseisms. pRg generated in the deep ocean have most of their energy in the ocean ("acoustic" pRg) and are continuously observed on the ocean bottom, but acoustic pRg does not efficiently transition onto continents. High‐amplitude DF signals over the [0.2, 0.3] Hz band observed on the deep seafloor are uncorrelated with continental observations and are not clearly detectable at individual continental stations or by land seismic‐array beamforming. Below 0.2 Hz, modeling and some observations suggest that some deep water‐generated elastic pRg energy can reach continental stations, providing that losses from scattering and transition across the continental‐shelf boundary to the shore are not substantial. However, most observations indicate that generally little deep‐ocean‐generated DF microseism energy reaches continental stations. Effectively, DF land observations are dominated by near‐coastal wave activity.